Impor Gula Mentah (Raw Sugar) Versus Swasembada Gula - Pantja Siwi; Budi Handojo (Sekolah Tinggi Maritim Yogyakarta, 2019)
White Crystal Sugar (GKP) is the second most demanded food commodity in Indonesia after rice. The demand of GKP rises with the increasing population. National demand of sugar comprises of direct consumption (household) and indirect needs (food, beverage and pharmaceutical industries). In the last five years, the demand for sugar in household consumption has been relatively stable. In contrast, the demand for industrial sugar is increasing and the overall demand for sugar surpasses national sugar production. Efforts made by the government at this time including importing sugar and preparing for the achievement of self-sufficiency in household sugar consumption scheduled for 2019. Implementing both policies are challenging due to the declines in ​​sugarcane fields and productivity. Our Dutch-heritage factories must be revitalized whereas building a new sugar factory (PG) is costly as well as research. Therefore, the effort that can be done quickly is importing sugar for industrial demand in form of raw sugar (Raw Sugar).